Zero waste lifestyle concept within Islamic-science prespective - Alvi Jauharotus Syukriya; Lensa Rosdiana Safitri (Universitas Airlangga, 2021)
Islam has comprehensive rule that regulate in all aspects of human life, including evireonmental issues. One fact of global problems related to environment is waste management problem. Zero waste is waste management system which it could be a holistic solution due to waste issue. This study aim to analyse the zero waste concept within Islamic-science prespective on municipal waste reduction as a solution to prevent environmental damage. This study use literature reviews method that focuse on waste management programs in Surabaya City which have been stated on a national and international scale. The results of this study show implementation of waste management programs In Surabaya City such as the depletion of disposable plastic usage, the existence of waste bank units, until the presence of a solid waste power plant infrastructure. However, the program implementation has not been able to decrease the number of resource in Surabaya landfill. It is because of poorly coordination between government and society, and the lack of environmental awareness about the harm of waste resource to environmental health. Thus, the existence of zero waste concept combined with Islamic-science prespective could lead direction movement to appreciate the importance of proper and correct waste management. Based on these results, it conclude that waste management with zero waste concept considered to become a new lifestyle in waste management namely Islamic lifestyle, because it is in line with Islamic law. Moreover, this new lifestyle could be implemented in all communities regarding to the nature is a gift form Allah SWT and humans have a command to protect it.